2018
DOI: 10.1021/acsami.7b16192
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Bead Sandwich Assay Based on a Split Aptamer

Abstract: A few aptamers still bind their targets after being split into two moieties. Split aptamers have shown great potential in the development of aptameric sensors. However, only a few split aptamers have been generated because of lack of knowledge on the binding structure of their parent aptamers. Here, we report the design of a new split aptamer and a flow cytometric bead sandwich assay using a split aptamer instead of double antibodies. Through DMS footprinting and mutation assay, we figured out the target-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…For structure-switching aptamers, some improvements have been developed based on fluorescence resonance energy transfer (FRET). Shen et al split a DNA aptamer into two parts for target detection 38 . One part was labeled with biotin and the other with a fluorophore.…”
Section: Potential Utility Of Aptamer Technology For Pathogen Detectionmentioning
confidence: 99%
“…For structure-switching aptamers, some improvements have been developed based on fluorescence resonance energy transfer (FRET). Shen et al split a DNA aptamer into two parts for target detection 38 . One part was labeled with biotin and the other with a fluorophore.…”
Section: Potential Utility Of Aptamer Technology For Pathogen Detectionmentioning
confidence: 99%
“…Although the PTB7-Th : PC 71 [35] Shen et al recently managed to considerably increase that value ( Figure 5(b)). [36] The authors employ photonic crystals acting as Bragg reflectors to balance the transmitted colors and increase the CRI of their reference device (CRI = 91) up to 95 while maintaining an AVT of 20 %. However, starting with active layers that homogeneously absorb throughout the visible will remove the necessity for additional photonic crystal-like structures engineering.…”
Section: A Compromise Between High Performances and High Avt In Unifomentioning
confidence: 99%
“…On the other hand, including photonic crystals within the device architecture for light manipulation can enhance the PSC performances but generally leads to a reduction in transmitted light. [36,42,43] To ensure that PSC-based PWs are one day commercialized, other aspects have to be taken into account such as the production cost and the sustainability of the fabrication process. [44] In Section 3, I will review some techniques for eco-friendly and sustainable active layer fabrication.…”
Section: A Compromise Between High Performances and High Avt In Unifomentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al constructed a ratiometric electrochemical sensor based on a mismatched catalytic hairpin assembly for the detection of microRNA . In addition, recent work demonstrated that the signal background could be reduced by splitting the aptamer . Zheng et al developed a DNA nanoprobe for ATP based on FRET between the strands of a split aptamer .…”
Section: Introductionmentioning
confidence: 99%